Safe Liposuction: Case Report and Review of the Literature - Černauskis, Karolis; Kružyk, Sandra; Šukytė, Gabrielė; Venclauskas, Linas; Sakalauskas, Mantas (Lietuvos chirurgija, 2020)
Introduction. Liposuction is one of the most popular aesthetic surgical procedures. Liposuction is associated with weight loss, but the primary significance of this operation is body lines contouring. According to US plastic surgery statistics for 2018, liposuction surgery was ranked in the top five of cosmetic surgical procedures, and the most common area of suction in the body was the abdomen. One of the most difficult complications after this procedure is perforation of the small or large intestine, with a frequency of 0.014%. In order to avoid this complication, a comprehensive pre-operative, post-operative examination of the patient and ensuring the safety of the operation are important. We presenting a complicated clinical case of liposuction and literature review. Presentation of case report. In July 2019, a 49-year-old patient underwent surgery by plastic surgeons. Abdominal liposuction surgery was performed. On the first postoperative day, the patient complained of diffuse abdominal pain (VAS 7–8 points), but there were no clinical signs of peritonitis. The patient underwent urgent surgery following the development of a clinical picture of sepsis and peritonitis due to tomography. The operation started with diagnostic laparoscopy. On the left side of the abdominal wall, 4–5 mm abdominal wall defects were observed, and the intestinal cavity was rich in intestinal contents. No obvious injuries to the small intestine, colon or other abdominal organs were observed during laparoscopy. Therefore, a laparotomy was performed, during which two perforations of the small intestine were found and sutured. The postoperative period was smooth, with the patient discharged home after 11 bed days. Conclusions. Intestinal perforation after liposuction is a rare but dangerous complication. Although bowel injury is one of the most severe complications. Prevention is possible starting with a detailed clinical examination of the patient in the preoperative period. The postoperative period should be particularly important in light of the patient’s complaints and clinical symptoms. The presented clinical case shows what a complication of abdominal liposuction can be threatening and how important its early diagnosis and vigilance are.
Keywords: liposuction; perforation; peritonitis